Effects of Slow Coronary Artery Flow on QT Interval Duration and Dispersion - Atak, Ramazan (Ann Noninvasive Electrocardiol, 2003)
Background: The coronary slow‐flow phenomenon is an angiographic phenomenon characterized by delayed opacification of vessels in the absence of any evidence of obstructive epicardial coronary disease. Several studies have demonstrated myocardial ischemia in patients with slow coronary artery flow. In the present study, we aimed at evaluating the effects of slow coronary artery flow on QT interval duration and QT dispersion as a possible indicator of increased risk for ventricular arrhythmias and sudden cardiac death. Methods: The study population included 49 patients with angiographically proven normal coronary arteries and slow coronary flow in all three coronary vessels (group I, 33 males, 16 females, mean age = 48 ± 9 years), and 71 patients with angiographically proven normal coronary arteries without associated slow coronary flow (group II, 47 males, 24 females, mean age = 50 ± 8 years). Coronary flow rates of all subjects were documented by thrombolysis in myocardial infarction frame count (TIMI frame count). QT interval duration and QT dispersion of all subjects were measured on the standard 12‐lead electrocardiogram. Results: There was no statistically significant difference between the two groups in respect to age, gender, presence of hypertension, and diabetes mellitus. There was a significant difference between the two groups in respect to the presence of cigarette smoking, typical angina, and positive exercise test results. TIMI frame counts of group I patients were significantly higher than those of group II patients for all three coronary arteries (P < 0.001). Maximum corrected QT interval (QTcmax) of group I did not differ from the QTcmax of group II (P > 0.05). However, minimum corrected QT interval (QTcmin) of group I was significantly lower than that for group II (P = 0.008). Consequently, corrected QT dispersion (QTcd) in group I was found to be significantly higher than in group II (P < 0.001). Conclusion: QTcd, indicating increased risk for ventricular arrhythmias and cardiovascular mortality, was found to be significantly higher in patients with slow coronary artery flow. However, further long‐term prospective studies should be carried out to establish the significance of QTcd as a risk factor for ventricular arrhythmias and subsequent sudden cardiac death in patients with slow coronary artery flow.